Penerapan Nilai Pancasila dalam Budaya Disiplin dan Tanggung Jawab Siswa SMK PAB 8 Sampali: Penelitian - Anggi Karya Ningpasti; Ayu Swandana; Dina Rosanna Sipahutar; Fauziah Fauziah; Grachya Hanna Lory Saragih; Muhammad Sanny Islami Fasha; Nur Idaman Lase; Yeni Eriska Sihotang; Julia Ivanna (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to describe the application of Pancasila Philosophy values ​​in forming a culture of discipline and responsibility of students at SMK PAB 8 Sampali, identifying supporting and inhibiting factors, in order to improve Pancasila-based character education. The research method uses a descriptive mixed method approach with a Likert scale questionnaire strategy survey to 30 students in one class and a semi-structured interview to one PPKn teacher, analyzed through simple linear regression, descriptive analysis, and triangulation of primary (questionnaire and interview) and secondary (school document) data. The results show a very significant influence of the value of Pancasila application (X) on the culture of discipline and responsibility of students (Y). Values ​​such as divinity, humanity, unity, democracy, and social justice are internalized through habituation, teacher role models, and school regulations, despite facing obstacles such as gadget addiction, individualism, broken homes, and decreased student attendance. Thus, the study states that strengthening the internalization of Pancasila consistently through school culture is effective in building the character of students who are disciplined, responsible, and ready to face environmental challenges.